KEPATUHAN WAJIB PAJAK ORANG PRIBADI: PERAN PENGETAHUAN PAJAK, TRANSPARANSI INFORMASI, MODERENISASI TEKNOLOGI PELAYANAN PAJAK, DAN SANKSI PAJAK - Adiarta, Pratiwi; Putri, Nova Zamitah (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This research aims to analyze the influence of the variables of tax knowledge, tax sanctions, information transparency and tax technology modernization on individual taxpayer compliance in Indonesia. Primary data was collected through a questionnaire distributed to active taxpayers consisting of 104 respondents from various demographic groups. The method used in the research is convenience sampling. Data analysis uses multiple regression analysis data. The test results show that 1) Tax knowledge has a significant positive effect on taxpayer compliance, 2) Tax sanctions have a significant positive effect on taxpayer compliance, 3) Technological modernization has a significant positive effect on mandatory compliancetax, 4) Information transparency has a significant positive effect on taxpayer compliance